A novel lnc-LAMC2-1:1 SNP promotes colon adenocarcinoma progression by targeting miR-216a-3p/HMGB3 - Ji, Fulong; Yao, Zhiwei; Liu, Chunxiang; Fu, Siqi; Ren, Bingbing; Liu, Yong; Ma, Lushun; Wei, Jianming; Sun, Daqing (Heliyon, 2022)
Single nucleotide polymorphisms (SNPs) was associated with altering the secondary structure of long non-coding RNA (lncRNA). Increasing reports showed that lnc-LAMC2-1:1 SNP played an important role in cancer development and invasion. This study is to elucidate the molecular function of lnc-LAMC2-1:1 SNP rs2147578 promoting tumor progression in colon adenocarcinoma (COAD). In this study, we found that the lnc-LAMC2-1:1 SNP rs2147578 was upregulated in COAD cell lines. Furthermore, lnc-LAMC2-1:1 SNP rs2147578 promoted colon cancer migration, invasion, and proliferation. Interestingly, lnc-LAMC2-1:1 SNP rs2147578 positively regulated HMGB3 expression via miR-216a-3p in colon cancer cells. Functional enrichment analysis showed that targeting genes of miR-216a-3p were enriched in regulating the pluripotency of stem cells, MAPK signaling pathway, TNF signaling pathway, neurotrophin signaling pathway, relaxin signaling pathway, and FoxO signaling pathway. Tumor Immune Estimation Resource (TIMER) database revealed that there was a significantly positive correlation between HMGB3 expression and the infiltration of CD8+ T cells, B cells, neutrophils, macrophages, and CD4+ T cells. Finally, HMGB3 overexpression was validated in external data. In conclusions, lnc-LAMC2-1:1 SNP rs2147578 was involved in promoting COAD progression by targeting miR-216a-3p/HMGB3, and this study will provide a novel molecular target for COAD. Colon adenocarcinoma; lnc-LAMC2-1:1 SNP; miR-216a-3p; HMGB3; Progression.